The Workplace Stretching Exercises as an Ergonomic Intervention to Reduce Musculoskeletal Disorders among Construction Workers - Prihanto, Ratna litza; Widjajati, Noeroel; Aderilla, Savira (Universitas STRADA Indonesia, 2025)
Musculoskeletal Disorders (MSDs) are complaints involving muscles and bones, ranging from sprains to chronic conditions that may lead to disability. Proper ergonomic implementation promotes workers’ health, comfort, and productivity, while poor ergonomics can increase MSD risk. This study aimed to analyze the effect of Workplace Stretching Exercise (WSE) on MSD complaints among construction workers in Malang Regency. A quantitative approach with a quasi-experimental pretest–posttest control group design was applied. Of 94 workers, 76 were selected using simple random sampling. Data covered individual (age, tenure, BMI, habits) and work-related factors (posture, duration, workload). The dependent variable was MSD complaints before and after WSE intervention. Statistical analysis using ordinal regression revealed a significant decrease in MSD complaints after WSE. Factors significantly associated with reduced MSDs included younger age, better posture, shorter work duration, lower workload, and the WSE intervention itself (p < 0.05).